Environment data processing for a data centre (1) - Yeo, Haw Lin (Nanyang Technological University, 2024)
Data centres have aided in the development of this ever-digitalising world due to the increasing need for processing and data storage capacities. The huge increase in the number of data centres worldwide has led to concerns for their impact on the environment due to their significant power consumption. Part of this environmental impact by data centres is contributed by the immense amount of heat energy generated by the data centre servers and cooling systems. Due to these concerns, systems have been developed to capture the heat generated by data centres, and from there, the need for methods to predict the heat generated by the data centres arise.